STRUKTUR DAN UNSUR KEBAHASAAN TEKS DESKRIPSI DALAM HASIL PENERAPAN METODE GUESSING GAME PADA PESERTA DIDIK KELAS VII SMP - Sofya Yulianti, Risa Dwi; Asropah, Asropah; Septiana, Ika (Universitas Islam Sumatera Utara, 2023)
The background of this research is to describe the structure and linguistic elements of the descriptive text correctly and well in the structure of the descriptive text in the application of the Guessing Game method to seventh grade students of junior high school. Therefore, with this research to discuss the structure and linguistic elements of the descriptive text by collecting data in the research. The formulation of the problem in this research is how to use the structure and linguistic elements of the descriptive text used by class VII students of junior high school? The purpose of this study is to describe the structure and linguistic elements of the descriptive text that has been used by students of class VII SMP properly and correctly so that students are able to write descriptive text. The data collection method in this study is to use a qualitative descriptive method. The technique for presenting the results of the data in this study is descriptive analysis. Based on this research, the results of the analysis can be concluded that in writing descriptive text, class VII SMP students have used the structure and linguistic elements of the descriptive text correctly.